The role of strategic planning in enhancing Quality of organizational performance: Analytical study of the opinions of a sample of workers in Ministry of Interior / Police College - Hamoudi Al Attar, Fouad; jabbar shltaagh, shojaa (Iraqi Journal for Administrative Sciences, 2024)
The research aimed to shed light on the role of strategic planning (strategic culture, strategic vision, strategic decisions, organized strategic planning) according to the Rogers & Wright scale, 1998:) in enhancing the quality of organizational performance (success, creativity) according to (Rowe, et. al, 2005) by examining a sample of workers in the Ministry of Interior / Police College, as the sample size reached (155) represented by (department directors, people directors, lecturers, training officers, training teachers) and the researcher used a questionnaire to measure these variables for this purpose. In analyzing and processing the data, the researcher relied on a number of statistical tools and methods, including the ready-made statistical software package (Spss-V.23) and (Amos-V.23), which are used to extract the results, and in light of the results and analyzes, the study reached a set of conclusions, the most important of which are, The existence of an impact of the strategic planning dimensions on the quality of the organizational performance, and the researcher presented a set of recommendations, the most prominent of which was the development of evaluation criteria for strategic plans at all levels from one period to another according to various measures, and adopted to discover deviations and errors